2013
DOI: 10.1111/bph.12318
|View full text |Cite
|
Sign up to set email alerts
|

AVE 0991, a non‐peptide mimic of angiotensin‐(1–7) effects, attenuates pulmonary remodelling in a model of chronic asthma

Abstract: BACKGROUND AND PURPOSEAVE 0991 (AVE) is a non-peptide compound, mimic of the angiotensin (Ang)-(1-7) actions in many tissues and pathophysiological states. Here, we have investigated the effect of AVE on pulmonary remodelling in a murine model of ovalbumin (OVA)-induced chronic allergic lung inflammation. EXPERIMENTAL APPROACHWe used BALB/c mice (6-8 weeks old) and induced chronic allergic lung inflammation by OVA sensitization (20 μg·mouse −1 , i.p., four times, 14 days apart) and OVA challenge (1%, nebulised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 47 publications
5
82
0
Order By: Relevance
“…Most reports showed that the airway responsiveness to methacholine, a muscarinic agonist analogous to carbachol, increased in asthmatic rats (Cho et al, 2004;Deng et al, 2013) whereas in our study, asthmatic rats showed a drastic fall in the airway responsiveness to carbachol similar to that reported by Rodrigues-Machado et al (Rodrigues-Machado et al, 2013), who provided a plausible explanation. Attenuated tracheal ring contractions suggest that the airways in these rats underwent an extensive remodelling, that prevented the contraction in response to muscarinic receptor stimulation.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
See 1 more Smart Citation
“…Most reports showed that the airway responsiveness to methacholine, a muscarinic agonist analogous to carbachol, increased in asthmatic rats (Cho et al, 2004;Deng et al, 2013) whereas in our study, asthmatic rats showed a drastic fall in the airway responsiveness to carbachol similar to that reported by Rodrigues-Machado et al (Rodrigues-Machado et al, 2013), who provided a plausible explanation. Attenuated tracheal ring contractions suggest that the airways in these rats underwent an extensive remodelling, that prevented the contraction in response to muscarinic receptor stimulation.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…So we generated cumulative concentration-response curves with carbachol (10 -10 to 10 -5 M), which is a muscarinic receptor agonist to get an insight about function and structural alterations of airways (Rodrigues-Machado et al, 2013). There was a significant attenuation of contraction in asthma rats (Fig.…”
Section: Restoration Of Airway Responsiveness By Diminazene Aceturatementioning
confidence: 99%
“…Recently, the therapeutic potential of ANG-(1-7) axis was highlighted by the development of an orally active nonpeptide Mas agonist, such as AVE 0991 and CGEN-865S. AVE 0991 showed beneficial effects in heart dysfunction, atherosclerosis, blood pressure, and pulmonary remodeling (53)(54)(55)(56). These observations further confirm the protective role of ANG-(1-7) in different models of cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 60%
“…Recently we demonstrated [38, 39] in a model of chronic asthma induced by ovalbumin (OVA) that asthmatic mice exhibited an increase in size and number of vessels within the airway wall, contributing to thickening of the wall. OVA mice also presented a significant increase in myocyte diameter of the right ventricle, suggesting that structural remodeling led to an increase in pulmonary vascular resistance and subsequent right ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%